Covid-19 and the Linguistic Landscape of Berlin - Panagiotatou, Eliza (Aegean Working Papers in Ethnographic Linguistics, 2022)
The aim of this paper is to explore the relation between the Covid-19 pandemic and the linguistic landscape of Berlin. The approach builds on a dynamic perspective, which sees the semiotic landscape of a city as an arena of contestation between different social groups with various interests. Berlin constitutes an interesting research site, as it is known for its superdiversity, the co-existence of numerous subcultures, as well as its variety of cultural and political centres. This paper aims at studying the manifestation of the pandemic on the linguistic landscape while focusing on the intersection between language, space, politics, and activist discourse. The data were collected during the so-called “second wave” of the pandemic and consist of posters, advertisements, stencils, and banners. In the analysis both the sign and the environment in which it is positioned are taken into consideration. While Covid-19 is a global phenomenon, which is expected to affect the linguistic landscape of most urban conglomerates, the focus of this article is set on local features and their relation to the city’s profile.